2017
DOI: 10.1186/s12903-017-0442-x
|View full text |Cite
|
Sign up to set email alerts
|

Intraoral scanners in dentistry: a review of the current literature

Abstract: BackgroundIntraoral scanners (IOS) are devices for capturing direct optical impressions in dentistry. The purpose of this narrative review on the use of IOS was to: (1) identify the advantages/disadvantages of using optical impressions compared to conventional impressions; (2) investigate if optical impressions are as accurate as conventional impressions; (3) evaluate the differences between the IOS currently available commercially; (4) determine the current clinical applications/limitations in the use of IOS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
461
1
29

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 530 publications
(550 citation statements)
references
References 123 publications
4
461
1
29
Order By: Relevance
“…Modern digital technology could help to improve patients’ acceptance and clinical success. In the last years, the use of digital intraoral optical scanner (IOS) has been shown to be a viable option for the rehabilitation of partial edentulous patients, even when associated to computer-guided template-assisted implant placement [1,2]. The clinician and the patient can benefit in terms of shorter treatment time if intraoral digital impression is used [2].…”
Section: Introductionmentioning
confidence: 99%
“…Modern digital technology could help to improve patients’ acceptance and clinical success. In the last years, the use of digital intraoral optical scanner (IOS) has been shown to be a viable option for the rehabilitation of partial edentulous patients, even when associated to computer-guided template-assisted implant placement [1,2]. The clinician and the patient can benefit in terms of shorter treatment time if intraoral digital impression is used [2].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have addressed these variables by examining the accuracy of intraoral scanners as follows: in narrow spaces such as those for crowns or bridges (Ahrberg et al, ; Hack & Patzelt, ; Omar Ali, ;Pradíes, Zarauz, Valverde, Ferreiroa, & Martínez‐Rus, ; Syrek et al, ); covering larger parts of the dental arch such as a quadrant (Ender, Zimmermann, Attin, & Mehl, ); and covering the complete arch (Andriessen, Rijkens, Van Der Meer, & Wismeijer, ; Ender, Attin, & Mehl, ; Ender & Mehl, ,; Flügge, Att, Metzger, & Nelson, ; Güth, Edelhoff, Schweiger, & Keul, ; van der Meer, Andriessen, Wismeijer, & Ren, ; Patzelt, Bishti, Stampf, & Att, ; Patzelt, Emmanouilidi, Emmanouilidi, Stampf, Strub, & Att, ; Zhang, Suh, & Lee, ). Although the accuracy values in these studies differ from one case to another, it has been demonstrated that digital impressions are sufficiently accurate in small spaces (Ahrberg et al, ; Amin et al, ; Ender, Attin, et al, ; Ender & Mehl, ; Ender, Zimmermann, et al, ; Joda & Brägger, ; Joda et al, ; Pradíes, Zarauz, et al, ; Sakornwimon & Leevailoj, ; Schepke, Meijer, Kerdijk, & Cune, ; Syrek et al, ; Zhang et al, ), and the improvements implemented in the new versions of the scanners are resulting in improved accuracy (Imburgia et al, ; Mangano et al, ). However, in large spaces with uniform features (with no geometric differentiation in the radius of curvature), such as those typically associated with edentulous patients, the results are less impressive.…”
Section: Introductionmentioning
confidence: 96%
“…Intraoral scanners were first introduced more than 30 years ago (Duret & Preston, ). Since then, continuous steps have been taken towards their development and nowadays, with the improvements implemented by new devices and software (Mangano, Gandolfi, Luongo, & Logozzo, ), together with social acceptance of these new technologies, conventional impressions are being replaced by digital ones (Güth, Keul, Stimmelmayr, Beuer, & Edelhoff, ; Güth et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Closed systems integrate and offer data acquisition, processing, and restoration manufacturing through the same company. Open systems, on the other hand, provide more leeway by allowing for the acquisition and sharing of digital data, along with its subsequent manufacturing by different companies …”
Section: Introduction To Digital Workflowmentioning
confidence: 99%